מישל מונטרלה – בין פסיכואנליזה לפמיניזם : A Forward to “Inquiry into Femininity” - חרובי, דינה (מכאן, 2010)
The article of Michèle Montrelay, "Recherches sur la Féminité" ("Inquiry into Femininity") first published in 1970, reflects the attempts, shared by psychoanalysis and feminism, to explore and theorize feminine sexuality. Montrelay's point of departure is the two contradictory theories regarding female sexuality – that of Freud and that of Ernest Jones. Montrelay analyzes these theories and brings them together, to suggest a fascinating and innovative synthesis. Her theory has interesting relations with various theories of her famous French contemporaries: Hélène Cixous, Julia Kristeva and Luce Irigaray – and it is important to read her work in relation to theirs. The Introduction is followed by an interview with Prof. Shirley Sharon-Zisser, which enables us to understand the Lacanian context and the contribution of Montrelay to the discourse on feminine sexuality.